Application of Constructivism Approach in the Learning of Initial Value Matter and Boundary Requirement Course - Suanto, Elfis; Armis, Armis (Journal of Educational Sciences, 2017)
The purpose of this research is to repair the mathematic learningprocess of Initial Value Matter and Boundary Requirement (IVMBR)course. The variables which have been examined (1) the activities of lecturerand students in learning process, (2) the development of student grades, and(3) the completeness of student result in studying of IVBVP. These actionshave been done in three cycles based on data’s analysis, we get the result (1)the lecturer and students activities in learning process have been improved,(2) the development of student grades is rather the same in three of thecycles, and (3) the student who could reach the studying completely. Afterfirst cycle, these students get A or B  increasing to 62,50,`4%, and aftersecond cycle, the completeness of study has increased to 66,67%, and afterthird cycle, the completeness of studying have increased to 75,00%. Basedon these informations, the constrctivism learning is good to use in learing ofIVMBR course.